1982
DOI: 10.1136/vr.110.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella multocida infection of cats on poultry farms

Abstract: Eight cats on six poultry farms, four of which had a history of recent turkey pasteurellosis were examined for Pasteurella multocida infection. Nine strains were recovered and serotyped and of these five were tested for virulence in chickens and mice. By comparison with a strain from a field outbreak in turkeys three cat strains were considered capable of causing poultry disease. These findings are discussed epidemiologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On premises O, the cat was trapped 5 months after the fowl cholera outbreak in the turkeys but may have been carrying P. multocida for some time. Cats are recognized carriers of P. multocida, with prevalence rates of up to 92% being recorded (3,11,20,25). However, their means of transmitting the organism to poultry is uncertain, as they are not normally though to attack turkeys (11).…”
Section: Rea Typementioning
confidence: 99%
See 2 more Smart Citations
“…On premises O, the cat was trapped 5 months after the fowl cholera outbreak in the turkeys but may have been carrying P. multocida for some time. Cats are recognized carriers of P. multocida, with prevalence rates of up to 92% being recorded (3,11,20,25). However, their means of transmitting the organism to poultry is uncertain, as they are not normally though to attack turkeys (11).…”
Section: Rea Typementioning
confidence: 99%
“…Cats are recognized carriers of P. multocida, with prevalence rates of up to 92% being recorded (3,11,20,25). However, their means of transmitting the organism to poultry is uncertain, as they are not normally though to attack turkeys (11). Contamination of feed and water with excretions containing the bacterium is a possibility.…”
Section: Rea Typementioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent investigation found different clones of P. multocida in each of four outbreaks of fowl cholera on a duck farm over a 2-year period (Muhairwa et al ., 2000), indicating that elimination of P. multocida from infected farms is possible even in duck farms with a low level of biosecurity, as might be expected for a pathogen that is easily inactivated by common disinfectants, sunlight, drying or heat, and that survives for a maximum of 30 days in the environment (Backstrand & Botzler, 1986;Glisson et al ., 2003). P. multocida may have persisted by colonization of the cats that were kept at both affected farms, as they may act as reservoirs of P. multocida that are virulent for poultry (Curtis & Ollerhead, 1982;Snipes et al ., 1988;Korbel et al ., 1992;Van Sambeek et al ., 1995;Glisson et al ., 2003). As the majority of avian, ovine, bovine and porcine respiratory tract infections are caused by different clones of P. multocida (Davies et al ., 2004), it seems unlikely that cats commonly act as a reservoir; transmission of P. multocida by cats and dogs needs to be investigated in more detail, as a recent study by Muhairwa et al (2001) suggested that P. multocida are not commonly exchanged between poultry and carnivores, even when they are kept in close contact.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, with the exception of swine and possibly cat isolates, most are avirulent for fowl (5,12). Once the disease is introduced into a flock, it spreads rapidly.…”
mentioning
confidence: 98%